Observer-based robust fuzzy control of nonlinear networked systems with actuator saturation - Xu, Shidong; Wen, Hao; Wang, Xiaoyu (ISA transactions, 2022)
In this article, the aim is to study the observer-based robust fuzzy control of nonlinear systems subject to actuator saturation via network communication. Unlike most existing results, system outputs are sufficiently processed by an adaptive event-triggered mechanism in an aperiodic sampling manner. By utilizing Takagi–Sugeno (T–S) fuzzy description, a fuzzy observer is established based on the sampled outputs suffering from network-induced delays. A saturated fuzzy control law is then derived from the estimated states of the observer. Moreover, by using ℒ∞ performance index, the adverse effect of persistent bounded disturbance is substantially attenuated. A novel Lyapunov functional, fully considering the characteristics of aperiodic event-triggered scheme and transmission delays, is investigated to analyze system stability and synthesize the desired controller. In view of the imperfect premise matching, the knowledge of asynchronous membership functions is imported into the derivation of a novel set of sufficient conditions for controller synthesis. Finally, the proposed observer-based control algorithm is verified by an illustrative example and simulation results. •An output-based aperiodic event-triggered scheme is developed.•ℒ∞ performance is utilized to attenuate external disturbances.•A novel Lyapunov functional is proposed.